2000
DOI: 10.1046/j.1365-2982.2000.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fentanyl, DNQX and MK‐801 on dorsal horn neurones responsive to colorectal distension in the anaesthetized rat

Abstract: Certain dorsal horn neurones respond in a graded manner to noxious colorectal distension (CRD). Morphine inhibits these responses in the spinalized rat, but the role of excitatory amino acids in baseline visceral nociceptive transmission is less clear. This study examines the effect of the mu-opiate receptor agonist fentanyl, and the non-NMDA and NMDA antagonists DNQX and MK-801, respectively, on such responses to CRD in the sodium pentobarbitone-anaesthetized rat. Male rats were prepared for extracellular rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…Other investigators have shown that in naïve, adult rats without hyperalgesia, the AMPA receptor antagonist CNQX, differentially modified the activity of these two classes of neurons based on graded intensities of colon distension, having some effect on SL-A neurons (Ji and Traub, 2002). Another study in adult, naïve rats, demonstrated that the AMPA receptor antagonist DNQX, and not the NMDAR antagonist MK-801, decreased the responses of SL-A spinal neurons to CRD (Kozlowski et al, 2000). However, in a model of urinary bladder distension (Catroman and Ness 2002), three clinically available NMDAR antagonists (ketamine, dextromethorphan, and memantine) all demonstrated an inhibitory effect only on type I spinal neurons and not type II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have shown that in naïve, adult rats without hyperalgesia, the AMPA receptor antagonist CNQX, differentially modified the activity of these two classes of neurons based on graded intensities of colon distension, having some effect on SL-A neurons (Ji and Traub, 2002). Another study in adult, naïve rats, demonstrated that the AMPA receptor antagonist DNQX, and not the NMDAR antagonist MK-801, decreased the responses of SL-A spinal neurons to CRD (Kozlowski et al, 2000). However, in a model of urinary bladder distension (Catroman and Ness 2002), three clinically available NMDAR antagonists (ketamine, dextromethorphan, and memantine) all demonstrated an inhibitory effect only on type I spinal neurons and not type II.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported a similar effect on SL-S neurons in a model of visceral hyperalgesia induced by acute inflammation of the colon (Ness and Gebhart, 2000). It has also been suggested that these subtypes of neurons respond differently to pharmacological intervention (Ji and Traub 2002; Kozlowski et al, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Distension pressures of 10, 20, 40, 60 and 80 mmHg were routinely performed with 1 min between each stimulus. Responses were classified according to established criteria 2 , 4 . Isobaric, rather than isovolumetric stimuli were used to avoid mistaking genuine changes in response during bile infusion for changes in colonic wall compliance.…”
Section: Methodsmentioning
confidence: 99%
“…A considerable degree of processing occurs in the dorsal horn before information is directed to areas of the brain via ascending tracts in the dorsal and lateral spinal white matter 2 , 3 . Understanding of the pharmacology of this pathway has emerged recently 4 . Emphasis has been placed on processing of nociceptive mechanosensory afferent input.…”
Section: Introductionmentioning
confidence: 99%
“…In the rat, the NMDA glutamate receptor subtype is involved in a lumbosacral inhibitory mechanism controlling bladder activity (36,38), whereas the AMPA-kainate subtype controls 1) the activation of spinal neurons induced by colorectal distension (16) and 2) the frequency of spontaneous and perineal stimulation-evoked bladder contractions (36). Thus NMDA and AMPA-kainate receptors participate to the spinal control of pelvic organs.…”
mentioning
confidence: 99%